Partir de l’« expérience vécue » pour comprendre l’activité humaine - Géraldine Rix-Lièvre; Béatrice Cahour; Julien Guibourdenche (Revue d'anthropologie des connaissances)
This introductory article begins by situating the study of lived experience within situated, embodied and distributed approaches to cognition. It then reviews the history of the development of methods for investigating lived experience, as well as the articulation of intrinsic and extrinsic perspectives and different levels of description of activity. These positions make it possible to present the various articles in this thematic issue, highlighting their contribution to 'multi-method' and 'multi-level' articulations. Finally, this introduction shows that articulatory methodological approaches appear to be particularly relevant for tackling transformative issues and investing certain objects rooted in a embedded, embodied, extended and enacted conception of cognition.